2018
DOI: 10.1021/acs.jpcc.8b08846
|View full text |Cite
|
Sign up to set email alerts
|

Unveiled the Source of the Structural Instability of HKUST-1 Powders upon Mechanical Compaction: Definition of a Fully Preserving Tableting Method

Abstract: Metal–organic frameworks (MOFs) are getting closer to finally being used in commercial applications. In order to maximize their packing density, mechanical strength, stability in reactive environments, and many other properties, the compaction of MOF powders is a fundamental step for the application field of research of these extraordinary materials. In particular, HKUST-1 is among the most promising and studied MOF. Contrary to what reported so far in the literature, here we prove that the tableting of HKUST-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 45 publications
3
46
0
Order By: Relevance
“…This suggests that the water present within the pores might act as a "cushion" and help to evenly dissipate the applied pressure, preventing the collapse of the framework during compression. Similar behaviour was previously reported for MOF-5 [18] and HKUST-1 [19,20]. The durability of the pellets prepared using the…”
Section: Resultssupporting
confidence: 86%
“…This suggests that the water present within the pores might act as a "cushion" and help to evenly dissipate the applied pressure, preventing the collapse of the framework during compression. Similar behaviour was previously reported for MOF-5 [18] and HKUST-1 [19,20]. The durability of the pellets prepared using the…”
Section: Resultssupporting
confidence: 86%
“…In agreement, McKellar et al reported variations of 2.6% for densification pressures of 3.9 GPa [ 50 ]. Likewise, the non-appearance of new crystalline peaks indicates that the cubic structure is maintained [ 51 , 52 ]. Therefore, the pressure effect on Basolite C300 consists of crystallinity destruction, in agreement with the BET surface area and pore volume reduction with the pressure, but remaining unaltered the cubic structure of unaltered cells.…”
Section: Resultsmentioning
confidence: 99%
“…[4,[11][12][13][14][15][16][17][18][19][20][21] Recently, after many unsuccessful attempts, [4,[11][12][13] it has been found that HKUST-1 (or Cu-BTC), which is considered a reference system for all of the copper paddle wheel MOFs like STAM-17-OEt, is actually very easy to compact if the appropriate protocol is applied. [22] However, HKUST-1 is very sensitive to water and it typically undergoes severe hydrolysis even by limited exposure to air. [8,[22][23][24][25] In this work, we have tested the effectiveness of a similar compaction protocol to the water-proof and hemilabile STAM-17-OEt.…”
Section: Introductionmentioning
confidence: 99%
“…[22] However, HKUST-1 is very sensitive to water and it typically undergoes severe hydrolysis even by limited exposure to air. [8,[22][23][24][25] In this work, we have tested the effectiveness of a similar compaction protocol to the water-proof and hemilabile STAM-17-OEt. This latter Cu-based MOF, like HKUST-1, is formed by a paddle-wheel unit structure composed of two copper ions coordinated by four carboxylate bridges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation